2021
DOI: 10.1186/s40246-021-00330-7
|View full text |Cite
|
Sign up to set email alerts
|

Initial study on TMPRSS2 p.Val160Met genetic variant in COVID-19 patients

Abstract: Background Coronavirus disease 2019 (COVID-19) is a global health problem that causes millions of deaths worldwide. The clinical manifestation of COVID-19 widely varies from asymptomatic infection to severe pneumonia and systemic inflammatory disease. It is thought that host genetic variability may affect the host’s response to the virus infection and thus cause severity of the disease. The SARS-CoV-2 virus requires interaction with its receptor complex in the host cells before infection. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 32 publications
5
41
0
1
Order By: Relevance
“…For the association study, we searched for the studies on TMPRSS2 gene variants reported in the literature elsewhere in relation to COVID-19 susceptibility ( Mollica et al, 2020 ; Andolfo et al, 2021 ; Asselta et al, 2020 ; Bhattacharyya et al, 2020 ; Darbani, 2020 ; Hou et al, 2020 ; Irham et al, 2020 ; Iyer et al, 2020 ; Jeon et al, 2020 ; Kim and Jeong, 2021 ; Latini et al, 2020 ; Paniri et al, 2021 ; Piva et al, 2021 ; Ragia and Manolopoulos, 2020 ; Senapati et al, 2020 ; Sharma et al, n.d. ; Singh et al, 2021 ; Strope et al, 2020 ; Torre-Fuentes et al, 2021 ; Vargas-Alarcón et al, 2020 ; Wang et al, 2020 ; Wulandari et al, 2021 ; Saih et al, 2021 ; Schönfelder et al, 2021 ; Kehdy et al, 2021 ) from this a total of 5 SNPs (rs2070788, rs734056, rs12329760, rs2276205, and rs3787950) was observed in our data and studied subsequently in detail. Data from the Estonian Biocentre ( Chaubey et al, 2017 ; Pathak et al, 2018 ; Re3data, 2014 ; Tätte et al, 2019 ), phase 3 of the 1000 Genomes Project ( Durbin et al, 2010 ), and our new genotyped samples from several Indian states were used to calculate the frequency of each of these SNPs among various Indian populations using plink 1.9.…”
Section: Methodssupporting
confidence: 59%
“…For the association study, we searched for the studies on TMPRSS2 gene variants reported in the literature elsewhere in relation to COVID-19 susceptibility ( Mollica et al, 2020 ; Andolfo et al, 2021 ; Asselta et al, 2020 ; Bhattacharyya et al, 2020 ; Darbani, 2020 ; Hou et al, 2020 ; Irham et al, 2020 ; Iyer et al, 2020 ; Jeon et al, 2020 ; Kim and Jeong, 2021 ; Latini et al, 2020 ; Paniri et al, 2021 ; Piva et al, 2021 ; Ragia and Manolopoulos, 2020 ; Senapati et al, 2020 ; Sharma et al, n.d. ; Singh et al, 2021 ; Strope et al, 2020 ; Torre-Fuentes et al, 2021 ; Vargas-Alarcón et al, 2020 ; Wang et al, 2020 ; Wulandari et al, 2021 ; Saih et al, 2021 ; Schönfelder et al, 2021 ; Kehdy et al, 2021 ) from this a total of 5 SNPs (rs2070788, rs734056, rs12329760, rs2276205, and rs3787950) was observed in our data and studied subsequently in detail. Data from the Estonian Biocentre ( Chaubey et al, 2017 ; Pathak et al, 2018 ; Re3data, 2014 ; Tätte et al, 2019 ), phase 3 of the 1000 Genomes Project ( Durbin et al, 2010 ), and our new genotyped samples from several Indian states were used to calculate the frequency of each of these SNPs among various Indian populations using plink 1.9.…”
Section: Methodssupporting
confidence: 59%
“…TMPRSS2 act as co-receptor for SARS-CoV-2 cell invasion and it's high expression will lead to increased susceptibility for COVID-19. 32,33 The mean age of all the subjects in our study was 59 years old, with the youngest subject over 50 years old. Older people were more sensitive to SARS-CoV-2 infection and had a higher positive rate than younger age.…”
Section: Discussionmentioning
confidence: 91%
“…TMPRSS2 acts as a co-receptor for SARS-CoV-2 cell invasion, and its high expression will lead to increased susceptibility for COVID-19. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%